Clinical significance of lymph node size in locally advanced cervical cancer treated with concurrent chemoradiotherapy - Oh, Jinju (Yeungnam Univ J Med, 2019)
BACKGROUND: This study aimed to assess the in-field lymph node (LN) failure rate according to LN size and to investigate effect of LN size on the survival outcome of patients with locally advanced cervical carcinoma treated with concurrent chemoradiotherapy (CCRT). METHODS: A total of 310 patients with locally advanced cervical carcinoma treated with CCRT were enrolled in retrospective study. LN status was evaluated by magnetic resonance imaging. All patients received conventional external beam irradiation and high-dose rate brachytherapy, and concurrent cisplatin-based chemotherapy. In-field LN failure rate according to LN size was analyzed. RESULTS: The median follow-up period was 83 months (range, 3-201 months). In-field LN failure rate in patients with pelvic LN size more than 10 mm was significantly higher than that in patients with pelvic LN size less than 10 mm (p<0.001). A similar finding was observed in the in-field para-aortic LN (PALN) failure rate (p=0.024). The pelvic and PALN size (≥10 mm) was a significant prognostic factor of overall-survival (OS) and disease-free survival rate in univariate and multivariate analyses. The OS rate was significantly different between groups according to LN size (<10 mm vs. ≥10 mm). CONCLUSION: A LN of less than 10 mm in size in an imaging study is controlled by CCRT. On the other hand, in LN of more than 10 mm in size, the in-field LN failure rate increase and the prognosis deteriorate. Therefore, a more aggressive treatment strategy is needed.